Detection of Hepatitis B Virus X Gene Mutation from Local Clinical Samples - ANITA ARTARINI; HANARY G JESSICA; RADEN RINI KARTIKASARI; CATUR RIANI; DEBBIE S RETNONINGRUM (Indonesian Society for microbiology, 2016)
Hepatitis B virus (HBV) belongs to the Hepadnaviridae family and it infects hepatocytes, which is the most common cell in liver. HBV infection is distinguished into acute and chronic infection based on the duration of infection. Chronic infection of HBV exists more than six months and it can develop into liver cirrhosis and hepatocellular carcinoma (HCC). The development of chronic HBV infection is affected by viral particle load, genotype and subgenotype, as well as its association with HBV X gene mutation. The aim of this study is to determine the genotype and subgenotype based on X gene, and to detect its mutation. The X gene in DNA samples was amplified with nested PCR, which produced two fragments with size of 469bp and 395bp. The DNA sequencing results of the amplified product were analyzed by BLAST program to determine their HBV genotype and subgenotype based on the X gene sequences. The analysis showed that patients were infected mainly by HBV subgenotype B3, which are common in Indonesia. The obtained HBx gene sequences were aligned with HBx gene sequences from database to determine the genotype, subgenotype and amino acid substitution. In this study, we described the presence of known HCC-related HBx mutant, i.e. V5L, A47T, I127T and K130M/V131I, as well as new HBx mutant, i.e. G22S and A85T. The presence of HBx T118N mutant was detected at the highest percentage and occurred from samples with high HBV DNA titer.Â